Kurt A. Raaflaub, Josiah Ober y Robert W. Wallace. The Origins of Democracy in Ancient Greece. University of California Press, Berkeley and Los Angeles, 2007 - Bernat i Capdevila, Ernest (Foro Interno, 2009)
Sin resumen